Deep-subwavelength engineering of stealthy hyperuniformity - Park Jusung; Park Seungkyun; Kim Kyuho; Kwak Jeonghun; Yu Sunkyu; Park Namkyoo (Nanophotonics)
Light behaviours in disordered materials have been of research interest primarily at length scales beyond or comparable to the wavelength of light, because order and disorder are often believed to be almost indistinguishable in the subwavelength regime according to effective medium theory (EMT). However, it was demonstrated that the breakdown of EMT occurs even at deep-subwavelength scales when interface phenomena, such as the Goos–Hänchen effect, dominate light flows. Here we develop the engineering of disordered multilayers at deep-subwavelength scales to achieve angle-selective manipulation of wave localization. To examine the disorder-dependent EMT breakdown, we classify the intermediate regime of microstructural phases between deep-subwavelength crystals and uncorrelated disorder through the concept of stealthy hyperuniformity (SHU). We devise material phase transitions from SHU to uncorrelated disorder for distinct angular responses of wave localization by tailoring the short-range and long-range order in SHU multilayers. The result paves the way to the realization of deep-subwavelength disordered metamaterials, bridging the fields of disordered photonics and metamaterials.